Carbon quantum dots and preparation method thereof and application thereof in nitrogen-fixing microorganism bacillus

CN123002828APending Publication Date: 2026-10-30RES CENT FOR ECO ENVIRONMENTAL SCI THE CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611258908.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-19
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

然而,现有一步水热法体系合成碳量子点的技术方案仍存在以下问题:缺乏对碳晶核生长的调控,导致碳晶核生长过程较易发生无序聚并、产物粒径分布较宽、量子产率有限、缺陷态调控空间较小等问题

Benefits of technology

[0009]基于上述技术方案,本申请提供的碳量子点及其制备方法和在固氮微生物类芽孢杆菌(Paenibacillus sp.)SY6中的应用至少存在以下有益效果之一:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The application provides carbon quantum dots, a preparation method thereof and application thereof in nitrogen-fixing microorganisms bacillus, and belongs to the technical field of nanometer carbon materials. The preparation method of the carbon quantum dots comprises the following steps: dissolving citric acid, tea polyphenol and a nitrogen-containing dopant in water, adding metal salt-humic acid co-modified biochar, and obtaining a suspension after mixing; adding the suspension into a reactor to perform hydrothermal reaction, performing centrifugal separation, and obtaining supernatant; and performing filtration, dialysis and freeze-drying on the supernatant to obtain the carbon quantum dots; wherein the metal salt-humic acid co-modified biochar is obtained by modifying biochar with metal salt and humic acid, and the metal salt is selected from iron salt or aluminum salt.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of carbon nanomaterials, and more particularly to a carbon quantum dot, its preparation method, and its application in nitrogen-fixing microorganisms such as Bacillus. Background Technology

[0002] Carbon quantum dots (CDs), as a type of zero-dimensional carbon nanomaterial, have shown great potential in fields such as biological tracing and microecological regulation due to their excellent water solubility, unique photoelectric properties, good biocompatibility and low toxicity.

[0003] Currently, the one-step hydrothermal method is one of the commonly used methods for synthesizing carbon quantum dots. However, the existing one-step hydrothermal method for synthesizing carbon quantum dots still has the following problems: lack of control over the growth of carbon nuclei, which leads to disordered aggregation of carbon nuclei, wide particle size distribution of products, limited quantum yield, and small defect state control space.

[0004] Therefore, how to achieve multi-dimensional synergistic control over the growth of carbon crystal nuclei, surface chemical structure, and defect states of carbon quantum dots is of great scientific significance and application value for promoting the controllable preparation of carbon quantum dot materials and their functional applications in the field of agricultural microbiology (such as nitrogen fixation and promoting microbial growth). Summary of the Invention

[0005] In view of this, in order to at least partially solve at least one of the aforementioned technical problems, this application provides carbon quantum dots, a method for their preparation, and their application in the nitrogen-fixing microorganism Paenibacillus sp. SY6.

[0006] As a first aspect of this application, a method for preparing carbon quantum dots is provided, comprising: dissolving citric acid, tea polyphenols, and a nitrogen-containing dopant in water, adding metal salt-humic acid co-modified biochar, and mixing to obtain a suspension; adding the suspension to a reactor for hydrothermal reaction, centrifuging to obtain a supernatant; filtering, dialysis, and freeze-drying the supernatant to obtain carbon quantum dots; wherein, the metal salt-humic acid co-modified biochar is obtained by modifying biochar with metal salt and humic acid, and the metal salt is selected from iron salt or aluminum salt.

[0007] As a second aspect of this application, a carbon quantum dot is provided, which is prepared using the above-described method for preparing carbon quantum dots.

[0008] As a third aspect of this application, an application of carbon quantum dots in a nitrogen-fixing microorganism, Paenibacillus sp. SY6, is provided. This nitrogen-fixing microorganism, Paenibacillus sp. SY6, is deposited at the China General Microbiological Culture Collection Center (CGMCC) with accession number CGMCC No. 35901.

[0009] Based on the above technical solution, the carbon quantum dots and their preparation method provided in this application, and their application in the nitrogen-fixing microorganism Paenibacillus sp. SY6, have at least one of the following beneficial effects:

[0010] This application introduces metal salt-humic acid co-modified biochar as a carrier and carbon source for the confined synthesis of carbon quantum dots, and tea polyphenols and citric acid composite as organic carbon source precursors for carbon quantum dots. Combined with nitrogen-containing dopants, it achieves precise control over the ordered growth of carbon nuclei, surface chemical structure and energy level defect states of carbon quantum dots.

[0011] In this process, metal salt-humic acid co-modified biochar serves two main purposes. First, it acts as a carrier for confined hydrothermal reactions, providing a spatially confined environment for the formation and growth of carbon quantum dot nuclei through its pores, effectively inhibiting the disordered aggregation of carbon quantum dot nuclei. Second, the metal active sites on the metal salt-humic acid co-modified biochar and the quinone and phenolic hydroxyl functional groups in humic acid participate in synergistic catalysis, jointly constructing a carbon quantum dot surface chemical structure rich in oxygen- and nitrogen-containing functional groups and energy level defect states, together with citric acid, tea polyphenol carbon precursors, and nitrogen-containing dopants. Through this multi-dimensional synergistic regulation, the carbon quantum dots are ultimately endowed with excellent electron transport performance and nitrogen fixation enhancement properties.

[0012] These carbon quantum dots possess rich surface chemical structures and energy level defect states, multi-band fluorescence, and good biocompatibility. Their application in the nitrogen-fixing microorganism Paenibacillus sp. SY6 significantly improves nitrogen fixation efficiency and promotes strain growth. Attached Figure Description

[0013] Figure 1 The images show the fluorescence characteristics of carbon quantum dots prepared in Example 1 of this application, wherein (a) is a fluorescence photograph of carbon quantum dots under ultraviolet light irradiation at different wavelengths; (b) is a fluorescence excitation spectrum of carbon quantum dots; and (c) is a fluorescence emission spectrum of carbon quantum dots.

[0014] Figure 2This is a characterization diagram of the promoting effect of carbon quantum dots on the growth of nitrogen-fixing microorganism Paenibacillus sp. SY6 in Example 1 of this application, wherein (a) is the OD at different culture times and different carbon quantum dot addition ratios. 600 (a) A curve of values; (b) Flow cytometry plots at different culture times and different carbon quantum dot addition ratios;

[0015] Figure 3 This is a comparison diagram of the nitrogenase activity of carbon quantum dots prepared in Example 1 and Comparative Example 1 of this application in the nitrogen-fixing microorganism Paenibacillus sp. SY6;

[0016] Figure 4 This is a comparison chart showing the microbial nitrogen assimilation efficiency of carbon quantum dots prepared in Example 1 and Comparative Example 1 of this application in the nitrogen-fixing microorganism Paenibacillus sp. SY6.

[0017] The aforementioned nitrogen-fixing microorganism, Paenibacillus sp. SY6, was deposited on September 12, 2025, at the China General Microbiological Culture Collection Center (CGMCC), located at No. 3, Courtyard 1, Beichen West Road, Chaoyang District, Beijing, Institute of Microbiology, Chinese Academy of Sciences, with accession number CGMCC No. 35901 and deposit date of September 12, 2025. Detailed Implementation

[0018] To make the objectives, technical solutions, and advantages of this application clearer, the following detailed description is provided in conjunction with specific embodiments and the accompanying drawings.

[0019] In realizing the concept of this application, it was found that existing carbon quantum dots lack effective control over carbon crystal nucleus growth, surface chemical structure, and energy level defect state structure, which restricts the practical application of carbon quantum dots in promoting microbial growth and improving nitrogen fixation efficiency.

[0020] Based on this, this application proposes a carbon quantum dot, its preparation method, and its application in the nitrogen-fixing microorganism *Paenibacillus sp.* SY6. By introducing metal salt-humic acid co-modified biochar as a porous carrier for the hydrothermal synthesis of carbon quantum dots, its abundant micropores and mesopores provide a spatially confined environment for the formation and growth of carbon quantum dot nuclei. Simultaneously, the quinone and phenolic hydroxyl functional groups in the metal salt and humic acid synergistically catalyze the process, and together with citric acid, tea polyphenol organic carbon precursors, and nitrogen-containing dopants, construct a carbon quantum dot surface chemical structure rich in oxygen- and nitrogen-containing functional groups and energy level defect states. The carbon quantum dots obtained by the above preparation method exhibit good nitrogen-fixing efficiency and applications in the nitrogen-fixing microorganism *Paenibacillus sp.* SY6.

[0021] As a first aspect of this application, a method for preparing carbon quantum dots is provided, comprising steps A1-A3.

[0022] Step A1: Dissolve citric acid, tea polyphenols, and nitrogen-containing dopant in water, add metal salt-humic acid co-modified biochar, and mix to obtain a suspension; wherein, the metal salt-humic acid co-modified biochar is obtained by modifying biochar with metal salt and humic acid, and the metal salt is selected from iron salt or aluminum salt.

[0023] Step A2: Add the suspension obtained in step A1 into the reactor for hydrothermal reaction, centrifuge to separate the supernatant.

[0024] Step A3: The supernatant obtained in step A2 is filtered, dialyzed, and freeze-dried to obtain carbon quantum dots.

[0025] In the embodiments of this application, through the synergistic effect of citric acid, tea polyphenol composite carbon precursor, nitrogen-containing dopant and metal salt-humic acid co-modified biochar confinement support, multi-dimensional precise control of carbon quantum dot carbon core ordered growth, surface chemical structure and defect state is achieved.

[0026] Specifically, the tea polyphenols selected in this application contain abundant phenolic hydroxyl groups, which, together with citric acid, serve as organic carbon source precursors. Nitrogen-containing dopants are introduced for heteroatom doping, thereby effectively controlling the conjugated framework structure and surface energy level defect state density of carbon quantum dots. Metal salt-humic acid co-modified biochar is obtained by modifying biochar with metal salts and humic acid. Utilizing its microporous-mesoporous structure, large specific surface area, and abundant surface functional groups, it provides a spatially confined environment for the hydrothermal reaction of carbon quantum dots, effectively suppressing the disordered aggregation of crystal nuclei in the homogeneous system. Citric acid, tea polyphenols, and nitrogen-containing dopants are added to water, mixed and dissolved, and then metal salt-humic acid co-modified biochar is added and mixed evenly. This allows the citric acid, tea polyphenol composite carbon precursor, and nitrogen-containing dopants to fully wet and penetrate the internal pores of the metal salt-humic acid co-modified biochar, forming a uniform suspension.

[0027] The above suspension was placed in a reactor for hydrothermal reaction. During the hydrothermal reaction, the metal salt-humic acid co-modified biochar enriched the active sites of metal species and quinone and carboxyl oxygen-containing functional groups. These can serve as a carrier and carbon source for confined hydrothermal reactions, synergistically promoting the nucleation and growth of carbon quantum dots. This results in richer surface chemical structures and more ordered carbon core structures in the carbon quantum dots, leading to their excellent nitrogen-fixing properties. The obtained hydrothermal reaction products were centrifuged, and the collected supernatant was post-processed through filtration, dialysis, and freeze-drying to obtain the carbon quantum dots.

[0028] In step A1, metal salts and humic acid modify biochar to obtain metal salt-humic acid co-modified biochar, which includes: mixing lignocellulosic biomass, metal salts, and humic acid in water and drying them, pyrolyzing them under an inert atmosphere, and then post-processing them to obtain metal salt-humic acid co-modified biochar; wherein the inert atmosphere includes at least one of nitrogen and argon.

[0029] In the embodiments of this application, lignocellulosic biomass is mixed with metal salts and humic acid in an aqueous phase, impregnated, and then dried, so that metal ions and humic acid are uniformly loaded on the surface and internal pores of the lignocellulosic biomass framework. Subsequently, pyrolysis is performed under an inert atmosphere, transforming the lignocellulosic biomass in situ into a porous carbon framework. Simultaneously, humic acid grafts oxygen-containing functional groups such as quinone and carboxyl groups onto the carbon framework surface, while metal ions are anchored in situ as highly dispersed metal active centers. After post-treatment, metal salt-humic acid co-modified biochar is obtained.

[0030] In some embodiments, lignocellulosic biomass includes at least one of corn stalks, rice stalks, wheat stalks, sorghum stalks, cotton stalks, peanut shells, corn cobs, rice husks, and bagasse. The aforementioned lignocellulosic biomass raw materials are widely available, inexpensive, and rich in cellulose, hemicellulose, and lignin. After pyrolysis, they can form abundant microporous-mesoporous structures, providing a stable basis for the preparation of biochar carriers with confined functions.

[0031] Furthermore, in some embodiments, the metal salt is selected from iron salts or aluminum salts. After pyrolysis, the iron salts or aluminum salts can be transformed in situ into highly dispersed metal active centers and anchored on the surface of the biochar carbon framework, thereby regulating its surface chemical structure and energy level defect states.

[0032] In some embodiments, the iron salt is selected from ferric chloride, ferric nitrate, ferric sulfate, and ferric citrate, and the aluminum salt is selected from any one or more of aluminum chloride, aluminum sulfate, and aluminum nitrate. Further, the metal salt is preferably ferric chloride, which acts as a Lewis acid site in the subsequent hydrothermal process, catalyzing the breaking of carbon-carbon bonds on the pore wall surface of the metal salt-humic acid co-modified biochar, promoting the participation of the carbon source in the growth of the carbon nucleus. Simultaneously, iron is used as Fe... 2+ / Fe 3+ The coordination state remains on the surface of carbon quantum dots, providing redox active centers for carbon quantum dots and regulating their surface chemical environment and energy level defect states.

[0033] Furthermore, the mass ratio of the aforementioned lignocellulosic biomass, metal salt, and humic acid is 10:2:1. At this ratio, the synergistic effect of the three components is optimal. Specifically, the sufficient proportion of lignocellulosic biomass ensures the formation of a continuous and complete carbon skeleton and abundant pores after pyrolysis. The metal salt at this ratio achieves high dispersion and anchoring, avoiding agglomeration. The appropriate amount of humic acid introduces sufficient quinone and carboxyl groups and other oxygen-containing groups without clogging the pores. After pyrolysis, the resulting metal salt-humic acid co-modified biochar possesses a rich microporous-mesoporous structure, highly dispersed metal active sites, and a suitable density of surface functional groups.

[0034] In some embodiments, the pyrolysis temperature for preparing metal salt-humic acid co-modified biochar is 500℃-700℃, preferably 600℃; the pyrolysis time is 1h-4h, preferably 2h. The pyrolysis temperature and time synergistically determine the pore structure and chemical properties of the metal salt-humic acid co-modified biochar. Specifically, if the pyrolysis temperature is too low (e.g., below 500℃), incomplete carbonization may occur, limiting pore growth. If the pyrolysis temperature is too high (e.g., above 700℃), excessive graphitization will occur, resulting in a significant loss of functional groups. Therefore, the preferred pyrolysis temperature is 600℃, which ensures sufficient carbonization while retaining an appropriate amount of oxygen-containing functional groups, forming a rich microporous-mesoporous structure. A pyrolysis time of less than 1h leads to insufficient pyrolysis, while a pyrolysis time exceeding 4h may cause pore collapse. Therefore, the optimal pyrolysis time is 2 hours, which ensures sufficient carbonization while maintaining the integrity of the pores, resulting in metal salt-humic acid co-modified biochar with a large specific surface area, good pore connectivity, and abundant surface functional groups, providing an ideal carrier for subsequent confined hydrothermal reactions.

[0035] In some embodiments, the post-treatment for preparing metal salt-humic acid co-modified biochar includes acid washing (e.g., dilute hydrochloric acid), deionized water washing, drying, and grinding.

[0036] Furthermore, in the post-treatment step of preparing metal salt-humic acid co-modified biochar, the drying temperature is 60℃-100℃, preferably 80℃; and the biochar is ground through a 100-mesh sieve. This setting removes moisture, and the grinding and sieving ensures uniform particle size, resulting in a large specific surface area for the obtained metal salt-humic acid co-modified biochar, which is beneficial for subsequent uniform mixing.

[0037] In the embodiments of this application, in step A1 of preparing carbon quantum dots, the mass ratio of citric acid to tea polyphenols is 4:1. At this ratio, citric acid, as a small-molecule carbon source, forms a dense carbon framework, ensuring the crystallinity and stability of the carbon core. Tea polyphenols, as large polyphenol molecules, partially retain their phenolic hydroxyl groups during carbonization, endowing the carbon quantum dots with abundant active sites and hydrophilic groups on the surface, and guiding the formation of energy level defect luminescent centers. This composite ratio avoids both excessive citric acid leading to a single surface functional group and excessive tea polyphenols causing a loose carbon core structure, ensuring that the carbon quantum dots possess high crystallinity, rich surface chemical structures, and excellent dispersibility.

[0038] In the embodiments of this application, the nitrogen-containing dopant includes any one or more of urea, ethylenediamine, and ammonia, preferably urea. All of the selected nitrogen-containing dopants can provide active nitrogen species under hydrothermal conditions, achieving covalent doping of nitrogen atoms in the carbon framework. Urea, in particular, exhibits a mild decomposition rate in hydrothermal systems, avoiding the destruction of the pore structure caused by violent gas production. Furthermore, its decomposition products participate in the carbonization reaction while effectively embedding nitrogen atoms into the carbon lattice in pyridine nitrogen and graphitic nitrogen configurations, increasing the density of surface defect states and surface active sites in carbon quantum dots. Moreover, the raw materials are readily available and inexpensive.

[0039] In the embodiments of this application, the total amount of citric acid and tea polyphenols is in a 1:1 mass ratio to the nitrogen-containing dopant. Within this ratio range, a balance between carbon nucleus construction and nitrogen doping can be synergistically achieved. Sufficient carbon precursor ensures full carbon nucleus growth, while an equal amount of nitrogen-containing dopant provides a sufficient nitrogen source to embed nitrogen atoms into the carbon lattice in pyridine nitrogen and graphitic nitrogen configurations, while avoiding excessive nitrogen-containing dopant residue that would complicate the subsequent dialysis process.

[0040] Furthermore, in the embodiments of this application, the mass ratio of citric acid, tea polyphenols, nitrogen-containing dopant, and metal salt-humic acid co-modified biochar is 4.5:4.5:5.0. At this mass ratio, the composite precursor formed by citric acid and tea polyphenols is present in equal amounts with the nitrogen-containing dopant, ensuring that carbon core construction and nitrogen doping are synchronized and synergistic. The proportion of metal salt-humic acid co-modified biochar is moderate, providing sufficient confined channels to constrain the carbon core particle size while avoiding excessive dilution of the organic carbon precursor concentration by the metal salt-humic acid co-modified biochar carrier, which could lead to insufficient carbon core growth. After the three components undergo a hydrothermal confinement reaction, the resulting carbon quantum dots exhibit high nitrogen doping efficiency and abundant surface functional groups, providing a structural basis for subsequent electron transfer and microbial applications.

[0041] In the embodiments of this application, in step A2, the temperature at which the suspension undergoes a hydrothermal reaction is 160℃-200℃, preferably 180℃; and the time for the hydrothermal reaction is 4h-12h, preferably 6h.

[0042] The temperature and time of the hydrothermal reaction synergistically regulate the nucleation, growth, and surface chemistry of carbon quantum dots: Below 160℃, precursor carbonization is insufficient; above 200℃, excessive carbon nucleus growth leads to uneven particle size and functional group decomposition. Therefore, the optimal hydrothermal reaction temperature is 180℃, which ensures carbonization efficiency while preserving active functional groups such as quinone / phenolic hydroxyl groups. A reaction time shorter than 4 hours results in incomplete reaction, while exceeding 12 hours leads to carbon nucleus aggregation and is unfavorable for defect state formation. Therefore, the optimal hydrothermal reaction time is 6 hours, which allows for sufficient carbonization and nitrogen doping while maintaining the confinement of pores to restrict carbon quantum dot growth. The synergistic effect of temperature and time in the hydrothermal reaction enriches the surface energy level defect states of carbon quantum dots, ensures efficient nitrogen doping, and preserves the integrity of surface functional groups, providing structural support for subsequent electron transport and nitrogen fixation enhancement.

[0043] In the embodiments of this application, in step A2, the obtained hydrothermal reaction product is centrifuged to precipitate large carbon deposits, and the supernatant is collected. Further centrifugation is performed at a speed of 8000-10000 r / min, preferably 10000 r / min; the centrifugation time is 10 min-30 min, preferably 15 min.

[0044] In step A3, the supernatant is filtered through a nylon microporous membrane with a specific pore size, then placed into a dialysis bag, and finally purified by dialysis in ultrapure water. Further, the nylon microporous membrane has a pore size of 0.22 µm, the dialysis bag has a molecular weight cutoff of 3500 Da, and the dialysis purification time is 72 h. During this period, the ultrapure water is replaced 2-3 times to thoroughly remove any residual free nitrogen-containing dopants. This completely avoids the risk of feedback inhibition of nitrogenase gene expression and catalytic activity due to the triggering of ammonium inhibition effects when used in applications such as nitrogen-fixing microorganisms. This ensures that carbon quantum dots can efficiently exert their growth-promoting and synergistic functions in subsequent applications such as microbial research.

[0045] Further, in the embodiments of this application, the supernatant is dialyzed to obtain dialysate, which is dispensed into vials, partially sealed with rubber stoppers, and pre-frozen in a -20°C ultra-low temperature freezer for 4-8 hours until the material is completely solidified, wherein the pre-freezing time is preferably 6 hours. Subsequently, it is freeze-dried in a vacuum freeze dryer, wherein the cold trap temperature is -40°C to -60°C, the vacuum degree is 20 Pa, and the vacuum freeze-drying time is 24-60 hours, preferably -60°C, and preferably 48 hours. Through the above steps, fluffy light brown carbon quantum dots can be obtained. The prepared carbon quantum dots are sealed and stored in a 4°C desiccator in the dark for later use. This effectively prevents moisture absorption, oxidation, and photodegradation, ensuring the long-term stability of the redispersibility, fluorescence properties, and biological activity of the carbon quantum dots in the aqueous phase.

[0046] As a second aspect of this application, a carbon quantum dot is provided, prepared by the above-described method. This carbon quantum dot exhibits a surface rich in oxygen-containing groups such as quinone and carboxyl groups, as well as nitrogen-containing groups, abundant energy level defect states, excellent water dispersibility, multi-band fluorescence, and good biocompatibility.

[0047] As a third aspect of this application, the application of carbon quantum dots in the nitrogen-fixing microorganism Paenibacillus sp. SY6 is provided.

[0048] In the embodiments of this application, the nitrogen-fixing microorganism Paenibacillus sp. SY6 was deposited on September 12, 2025, at the China General Microbiological Culture Collection Center (CGMCC), located at No. 3, Courtyard 1, Beichen West Road, Chaoyang District, Beijing, Institute of Microbiology, Chinese Academy of Sciences, with accession number CGMCC No. 35901 and deposit date of September 12, 2025.

[0049] In the embodiments of this application, the application concentration of the above-mentioned carbon quantum dots is 100 μg / mL-400 μg / mL, preferably 300 μg / mL. At this preferred concentration, nitrogen fixation efficiency can be significantly improved and strain growth can be promoted.

[0050] To further illustrate this application, the carbon quantum dots provided in this application, their preparation method, and their application in the nitrogen-fixing microorganism Paenibacillus sp. SY6 are described in detail below with reference to the embodiments. However, these descriptions should not be construed as limiting the scope of protection of this application.

[0051] Example 1

[0052] The preparation process of carbon quantum dots includes steps B1-B9.

[0053] Step B1: Raw material pretreatment: Take air-dried crop straw, crush it through a 40-mesh sieve, and dry it at 60℃ to constant weight for later use.

[0054] Step B2: Impregnation modification: According to the mass ratio of straw:FeCl3:humic acid of 10:2:1, each component is added to deionized water, stirred thoroughly, and impregnated for 12 hours, and then evaporated to dryness in a water bath at 80℃.

[0055] Step B3: Pyrolysis: Place the impregnated product in a tube furnace and heat it to 600℃ at a rate of 5℃ / min under a high-purity N2 atmosphere (flow rate 100mL / min), and pyrolyze it at this temperature for 2 hours.

[0056] Step B4: Post-processing: After cooling the pyrolysis product, wash it successively with 0.1 mol / L HCl and deionized water until the pH of the filtrate is neutral. After drying at 80°C, grind it through a 100-mesh sieve to obtain Fe-humic acid co-modified biochar powder, which is then sealed and stored for later use.

[0057] Step B5: Preparation of the mixture: Accurately weigh 3.6g of citric acid, 0.9g of tea polyphenols (the mass ratio of citric acid to tea polyphenols is 4:1) and 4.5g of urea, and dissolve them together in 100mL of ultrapure water. Stir thoroughly until the solution is clear. Then add 5.0g of the prepared Fe-humic acid co-modified biochar powder, stir magnetically for 30min, and then place it in an ultrasonic cleaner for ultrasonic treatment for 30min (ultrasonic power 240W) to promote the full penetration of citric acid, tea polyphenol molecules and urea into the internal micropores and mesopores of the biochar, forming a uniformly dispersed black suspension.

[0058] Step B6: Confined hydrothermal reaction: Transfer all of the above suspension to a 100mL high-pressure reactor with a polytetrafluoroethylene liner, seal and tighten it, and place it in a constant temperature heating box. Increase the temperature to 180℃ at 2℃ / min and perform a constant temperature hydrothermal reaction for 6 hours.

[0059] Step B7: Centrifugation and Collection: After the reaction is complete, allow the reaction vessel to cool naturally to room temperature. Transfer the product to a centrifuge tube and centrifuge at 10,000 r / min for 15 min to precipitate large carbon deposits. Collect the supernatant.

[0060] Step B8: Filtration and dialysis: After the supernatant is filtered through a 0.22µm nylon microporous membrane, it is placed into a dialysis bag with a molecular weight cutoff of 3500Da and purified by dialysis in ultrapure water for 72 hours. The ultrapure water is replaced regularly during the process to thoroughly remove residual free urea and ammonia nitrogen impurities.

[0061] Step B9: Freeze-drying and storage: The supernatant was filtered to obtain dialysate, which was dispensed into vials, partially sealed with rubber stoppers, and pre-frozen in a -20°C ultra-low temperature freezer for 6 hours until the material was completely solidified. Then, it was transferred to a vacuum freeze dryer (cold trap temperature -60°C, vacuum degree 20Pa) for freeze-drying for 48 hours to obtain a fluffy, light brown carbon quantum dot powder. This powder was sealed and stored in a desiccator at 4°C, protected from light, for later use. The carbon quantum dots prepared above are represented as N-CDs.

[0062] The carbon quantum dots prepared in Example 1 were diluted with ultrapure water to form an aqueous solution with a concentration of 20 μg / mL, and placed in a quartz cuvette for optical analysis. The specific analytical results are as follows: Figure 1 As shown.

[0063] Figure 1The fluorescence characteristics of carbon quantum dots prepared in Example 1 of this application are shown in the following diagrams: (a) is a fluorescence photograph of carbon quantum dots under ultraviolet light irradiation at different wavelengths; (b) is a fluorescence excitation spectrum of carbon quantum dots; and (c) is a fluorescence emission spectrum of carbon quantum dots.

[0064] like Figure 1 As shown in (a), under natural visible light irradiation, the aqueous solution of carbon quantum dots exhibits a clear, transparent, yellowish-brown color and excellent dispersibility. When placed in a dark chamber and excited by a 365 nm wavelength ultraviolet lamp, the aqueous solution of carbon quantum dots exhibits a bright and uniform blue fluorescence. When the excitation source is switched to a 405 nm wavelength, the solution exhibits a significant yellowish-green fluorescence. Using ultrapure water as a control group, it remains colorless and transparent under both 365 nm wavelength ultraviolet lamp and 405 nm wavelength excitation source irradiation. This multi-band luminescence characteristic indicates that the confinement reaction of Fe-humic acid co-modified biochar endows the carbon quantum dot surface with abundant energy level defect states and nitrogen- and oxygen-containing surface state luminescence centers.

[0065] The excitation and emission wavelengths of the above-mentioned carbon quantum dot aqueous solution were measured using ultraviolet fluorescence spectroscopy, and the results are as follows: Figure 1 (b) Figure 1 As shown in (c) in the figure.

[0066] like Figure 1 As shown in (b), the maximum excitation wavelength of the prepared carbon quantum dots is 570 nm, and the maximum emission wavelength is distributed at 637 nm. Figure 1 (c) indicates that the carbon quantum dot can capture visible light and emit red light. Its spectrum matches the light absorption characteristics of nitrogen-fixing bacteria, indicating that the catalytic efficiency of nitrogenase can be promoted through photoelectron transfer, thereby greatly improving the nitrogen fixation capacity and providing a new idea for light-driven nitrogen fixation enhancement.

[0067] In summary, the aqueous solution of carbon quantum dots prepared in Example 1 of this application has good dispersibility, is clear and transparent yellowish-brown under natural visible light, exhibits bright blue fluorescence under 365nm ultraviolet light excitation, and exhibits yellowish-green fluorescence under 405nm excitation. It has rich multi-band luminescence characteristics and can be used as an excellent bioluminescent probe material. It can also be applied to nitrogen fixation and growth promotion of nitrogen-fixing microorganisms.

[0068] Comparative Example 1

[0069] The preparation method of carbon quantum dots in Comparative Example 1 was the same as that in Example 1, except that Fe-humic acid co-modified biochar and tea polyphenols were not added. The carbon quantum dots prepared in Comparative Example 1 are represented by CDs.

[0070] Application Example 1

[0071] Example 1 of this application describes the application of carbon quantum dots prepared in Example 1 in the nitrogen-fixing microorganism Paenibacillus sp. SY6.

[0072] The nitrogen-fixing microorganism Paenibacillus sp. SY6 was deposited on September 12, 2025, at the China General Microbiological Culture Collection Center (CGMCC), Institute of Microbiology, Chinese Academy of Sciences, No. 3, No. 1 Beichen West Road, Chaoyang District, Beijing, with accession number CGMCC No. 35901 and deposit date of September 12, 2025.

[0073] (1) Preparation of standardized nitrogen-fixing microbial Paenibacillus sp. SY6 bacterial culture

[0074] The preparation method of the Dobereiner medium used in this application is shown in Table 1.

[0075] Table 1

[0076]

[0077] Table 1 shows that the pH of Dobereiner medium is 7.2. Adding 0.2g of peptone to the medium in Table 1 yields a low-nitrogen medium, adding 5g of peptone yields a high-nitrogen medium, and omitting peptone results in a nitrogen-free medium. Take a 500mL Erlenmeyer flask, add 200mL of low-nitrogen Dobereiner medium, and additionally add 0.2g / L soybean peptone to ensure initial microbial growth. After sterilizing the medium and cooling it to room temperature, add pure culture of the nitrogen-fixing microorganism *Paenibacillus* sp. SY6 at a 3% (v / v) volume ratio. Seal the flask with a breathable membrane and incubate at 30℃ and 150 rpm on a shaker for 2 days. Take the cultured bacterial suspension and dilute it to OD using sterile phosphate buffered saline (PBS, composition: NaCl: 136 mmol / L, KCl: 2.6 mmol / L, Na₂HPO₄: 8 mmol / L, KH₂PO₄: 2 mmol / L, pH = 7.2-7.4). 600 (Absorbance at 600 nm wavelength) = 1.0, and a standardized nitrogen-fixing microbial Paenibacillus sp. SY6 bacterial solution was obtained for later use.

[0078] (2) Experimental grouping and inoculation

[0079] A blank control group (pure culture of nitrogen-fixing microorganism Paenibacillus sp. SY6) without carbon quantum dots was set up, along with four experimental groups with different final concentrations of carbon quantum dot materials prepared in Example 1: Group A (100 μg / mL), Group B (200 μg / mL), Group C (300 μg / mL), and Group D (400 μg / mL). Each group was inoculated with 2% of the standardized nitrogen-fixing microorganism Paenibacillus sp. SY6 bacterial suspension (OD200) prepared above. 600 =1.0), and cultured under the same shaker conditions.

[0080] (3) Cell growth detection and analysis

[0081] ①OD 600 Curve determination: Samples were taken at regular intervals, and absorbance was measured using a UV spectrophotometer. Specific test results are as follows: Figure 3 As shown.

[0082] Figure 2 This is a characterization diagram of the promoting effect of carbon quantum dots on the growth of nitrogen-fixing microorganism Paenibacillus sp. SY6 in Example 1 of this application, wherein (a) is the OD at different culture times and different carbon quantum dot addition ratios. 600 (a) is a curve of the values; (b) is a flow cytometry graph of different culture times and different carbon quantum dot addition ratios.

[0083] like Figure 2 As shown in (a), the OD values ​​of groups A, B, C, and D, which contain carbon quantum dots prepared in Example 1, during the logarithmic and stationary phases are... 600 The values ​​were all significantly higher than those of the control group. Among them, group C (300 μg / mL) had the steepest growth curve and the highest biomass at the plateau phase; when the concentration was increased to 400 μg / mL (group D), the growth-promoting effect slightly declined.

[0084] ② Flow cytometry analysis: The carbon quantum dots prepared in Example 1 were co-incubated with a suspension of the nitrogen-fixing microorganism Paenibacillus sp. SY6. The suspension was then washed with PBS (components: NaCl: 136 mmol / L, KCl: 2.6 mmol / L, Na2HPO4: 8 mmol / L, KH2PO4: 2 mmol / L, pH = 7.2-7.4) and resuspended to a suitable concentration. The sample was loaded into a flow cytometer, and 10,000 events were collected at a low flow rate. Cell population density and particle characteristics were detected based on forward scattering (FSC) and side scattering (SSC) signals. Specific test results are as follows: Figure 2 As shown in (b) of the diagram.

[0085] like Figure 2As shown in (b) above, the results are consistent with OD. 600 The curves were basically consistent. Among them, after 48 hours, at a final concentration of 300 μg / mL carbon quantum dots, the community distribution pattern of intact, active cells was the densest, and the density of surviving and proliferating cells reached its maximum. These results indicate that the carbon quantum dots prepared in Example 1 of this application can effectively promote the growth of the nitrogen-fixing microorganism Paenibacillus sp. SY6, with an optimal working final concentration of 300 μg / mL.

[0086] Application Example 2

[0087] Application Example 2 of this application describes the application of carbon quantum dots in promoting nitrogenase activity.

[0088] Example 2 of this application uses the acetylene reduction method (ARA) to evaluate the effect of the carbon quantum dots prepared in Example 1 and Comparative Example 1 on the activation of microbial nitrogen fixation enzyme-catalyzed reduction catalysis. The specific process is as follows:

[0089] (1) System construction and inoculation

[0090] The optimal working concentration of carbon quantum dots was selected as 300 μg / mL. A blank control group containing *Paenibacillus sp.* SY6 was set up, along with experimental groups containing carbon quantum dots (N-CDs) prepared in Example 1 and carbon quantum dots (CDs) prepared in Comparative Example 1. All three groups were inoculated with 2% of the standardized *Paenibacillus sp.* SY6 bacterial suspension (OD) prepared in Example 1. 600 =1.0), and placed in a 50mL anaerobic bottle, sealed with a sterile rubber stopper to prevent gas exchange.

[0091] (2) Nitrogenase activity assay

[0092] Using a sterile syringe, 5% of the top air was drawn into the sealed culture system, and the same amount of 99% pure acetylene gas was injected. The system was then incubated at 30°C in the dark for 48 hours.

[0093] (3) Analysis of nitrogenase activity results

[0094] After incubation, concentrated hydrochloric acid was added to terminate the reaction. The gas inside the vial was extracted using a sterile syringe and stored in a 10 mL gas sample vial. The ethylene content generated by nitrogenase reduction was detected using gas chromatography-mass spectrometry (GC-MS). The test results are as follows: Figure 3 As shown.

[0095] Figure 3This is a comparison diagram showing the nitrogenase activity of carbon quantum dots prepared in Example 1 and Comparative Example 1 of this application in the nitrogen-fixing microorganism Paenibacillus sp. SY6.

[0096] like Figure 3 As shown, using the nitrogenase activity of the blank control group as a baseline (100%), the amount of acetylene reduced to ethylene per unit time in the carbon quantum dots (N-CDs) experimental group prepared in Example 1 was significantly increased, and its nitrogenase activity (ARA) was increased to 133%, which was significantly higher than the 57% of the carbon quantum dots (CDs) in Comparative Example 1. This indicates that the carbon quantum dots prepared in Example 1 of this application effectively stimulated the catalytic reduction potential of nitrogenase.

[0097] Application Example 3

[0098] Application Example 3 of this application describes the application of carbon quantum dots in improving the efficiency of microbial nitrogen assimilation.

[0099] This application example 3 uses... 15 Nitrogen stable isotope tracing technology was used to verify the promoting effect of carbon quantum dots on the actual nitrogen assimilation efficiency of microorganisms.

[0100] (1) System construction and inoculation

[0101] The experimental groups, working concentration of carbon quantum dots (300 μg / mL) and inoculation conditions (adding standardized nitrogen-fixing microorganism Paenibacillus sp. SY6 bacterial solution at a 2% inoculation rate) of Example 1 and Comparative Example 1 were exactly the same as those in Application Example 2, and were placed in a sealed 200 mL anaerobic bottle for incubation.

[0102] (2) Isotope labeling and determination

[0103] After evacuating the anaerobic bottle to a vacuum using a vacuum pump until a vacuum is achieved, immediately inject gas into the sealed anaerobic bottle. 15 An isotope tracer gas mixture of N2 and O2 in a 4:1 ratio was prepared and brought to atmospheric pressure. The anaerobic flask was incubated in the dark at 30°C for 80 hours. After incubation, the bacterial culture was centrifuged at 12,000 rpm, the supernatant was discarded, and the bacterial cells were collected. The cells were resuspended in sterile ultrapure water, washed, and centrifuged again at the same speed, after which the supernatant was discarded. The cells were then cryopreserved at -80°C and transferred to a vacuum freeze dryer (cold trap temperature -60°C, vacuum degree 20 Pa) for 48 hours.

[0104] (3) Results Analysis

[0105] Quantitative determination of stem cells using elemental analyzer-isotope ratio mass spectrometry (EA-IRMS) 15 The absolute cumulative abundance of nitrogen atoms was used to calculate the specific nitrogen fixation rate. Specific test results are as follows: Figure 4 As shown, where,15 The results of nitrogen stable isotope tracing directly reflect the physiological assimilation efficiency of gaseous nitrogen actually converted into cellular biomass. The test results are as follows: Figure 4 As shown.

[0106] Figure 4 This is a comparison chart showing the microbial nitrogen assimilation efficiency of carbon quantum dots prepared in Example 1 and Comparative Example 1 of this application in the nitrogen-fixing microorganism Paenibacillus sp. SY6.

[0107] like Figure 4 As shown, compared with the control group, the experimental group with added 300 μg / mL carbon quantum dots (N-CDs) prepared in Example 1 showed higher intracellular levels. 15 The enrichment of N increased significantly. 15 The nitrogen fixation rate was also increased to 293%, which is significantly higher than the 143% of the carbon quantum dots (CDs) prepared in Comparative Example 1, confirming that the carbon quantum dots prepared in Example 1 of this application effectively improved the ability of microorganisms to capture and assimilate inorganic nitrogen into nitrogen-containing organic matter.

[0108] In summary, the carbon quantum dots prepared in Example 1 of this application are non-toxic to nitrogen-fixing microorganisms (such as pure Paenibacillus sp. SY6) and can significantly promote their growth. 600 Growth curves and flow cytometry analysis both confirmed that the carbon quantum dots significantly increased the effective cell population density, with the optimal working concentration being 300 μg / mL. Furthermore, compared to Comparative Example 1, the carbon quantum dots prepared in Example 1 of this application significantly enhanced nitrogenase activity and specific nitrogen fixation rate, indicating that the citric acid, tea polyphenol composite carbon precursor, nitrogen-containing dopant, and metal salt-humic acid co-modified biochar confinement support in Example 1 of this application have a synergistic effect. This results in the carbon quantum dots of Example 1 possessing rich surface chemical structures and energy level defect states, thereby effectively stimulating the catalytic reduction potential of nitrogenase and the ability of microorganisms to capture and assimilate inorganic nitrogen gas into nitrogen-containing organic matter.

[0109] The specific embodiments described above further illustrate the purpose, technical solution, and beneficial effects of this application. It should be understood that the above descriptions are merely specific embodiments of this application and are not intended to limit this application. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the protection scope of this application.

Claims

1. A method for preparing carbon quantum dots, characterized in that, include: Citric acid, tea polyphenols, and nitrogen-containing dopants were dissolved in water, and metal salt-humic acid co-modified biochar was added. After mixing, a suspension was obtained. The suspension is added to the reactor for hydrothermal reaction, followed by centrifugation to obtain the supernatant. The supernatant was filtered, dialyzed, and freeze-dried to obtain carbon quantum dots; The metal salt-humic acid co-modified biochar is obtained by modifying biochar with metal salt and humic acid, wherein the metal salt is selected from iron salt or aluminum salt.

2. The preparation method according to claim 1, characterized in that: The metal salt-humic acid co-modified biochar is obtained by modifying biochar with the metal salt and humic acid, comprising: Lignocellulose biomass, metal salts, and humic acid are mixed in water, dried, and then pyrolyzed under an inert atmosphere. After post-treatment, the metal salt-humic acid co-modified biochar is obtained. The iron salt is selected from at least one of ferric chloride, ferric nitrate, ferric sulfate, and ferric citrate; The aluminum salt is selected from any one or more of aluminum chloride, aluminum sulfate, and aluminum nitrate.

3. The preparation method according to claim 2, characterized in that: The mass ratio of the lignocellulose biomass, the metal salt, and the humic acid is 10:2:

1.

4. The preparation method according to claim 2, characterized in that: The pyrolysis temperature is 500℃-700℃; The pyrolysis time is 1-4 hours.

5. The preparation method according to claim 1, characterized in that: The mass ratio of citric acid to tea polyphenols is 4:1; The nitrogen-containing dopant includes any one or more of urea, ethylenediamine, and ammonia. The total amount of citric acid and tea polyphenols is in a mass ratio of 1:1 to the nitrogen-containing dopant.

6. The preparation method according to claim 1, characterized in that: The mass ratio of the citric acid to the tea polyphenols, the nitrogen-containing dopant, and the metal salt-humic acid co-modified biochar is 4.5:4.5:5.

0.

7. The preparation method according to claim 1, characterized in that: The temperature of the hydrothermal reaction is 160℃-200℃; The hydrothermal reaction takes 4-12 hours.

8. A carbon quantum dot, characterized in that, It is prepared by the preparation method described in any one of claims 1 to 7.

9. The application of carbon quantum dots as described in claim 8 in the nitrogen-fixing microorganism Paenibacillus sp. SY6, characterized in that, The nitrogen-fixing microorganism Paenibacillus sp. SY6 is deposited at the China General Microbiological Culture Collection Center (CGMCC) with accession number CGMCC No. 35901.

10. The application according to claim 9, characterized in that: The application concentration of the carbon quantum dots is 100 μg / mL-400 μg / mL.